2021
DOI: 10.3847/1538-4365/ac1356
|View full text |Cite
|
Sign up to set email alerts
|

The Large Early Galaxy Astrophysics Census (LEGA-C) Data Release 3: 3000 High-quality Spectra of K s -selected Galaxies at z > 0.6

Abstract: We present the third and final data release of the Large Early Galaxy Astrophysics Census (LEGA-C), an ESO/VLT public spectroscopic survey targeting 0.6 < z < 1.0, Ks-selected galaxies. The data release contains 3528 spectra with measured stellar velocity dispersions and stellar population properties, a 25-fold increase in sample size compared to previous work. This K s -selected sample probes the galaxy population down to ∼ 0.3L * , for all colors and morphological types. Along with the spectra we publish a v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(10 citation statements)
references
References 69 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…We exclude sources with FLAG_SPEC = 2, that indicates that the photometry based flux calibration showed significant imperfections, compromising the measurement of absorption and emission indices (sect. 4.2 in van der Wel et al 2021). We further exclude sources with FLAG_MORPH = 1 or 2.…”
Section: Final Lega-c Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…We exclude sources with FLAG_SPEC = 2, that indicates that the photometry based flux calibration showed significant imperfections, compromising the measurement of absorption and emission indices (sect. 4.2 in van der Wel et al 2021). We further exclude sources with FLAG_MORPH = 1 or 2.…”
Section: Final Lega-c Samplesmentioning
confidence: 99%
“…Finally, we use line indices only for galaxies that have a measured stellar velocity dispersion (sect. 3.4 in van der Wel et al 2021). These criteria reduce the number of X-ray AGN to 94 and the number of galaxies to 2834, within 0.6 < z < 1.3.…”
Section: Final Lega-c Samplesmentioning
confidence: 99%
“…4.2). For that purpose, we cross-match our AGN and galaxies in the control sample with the LEGA-C catalogue (van der Wel et al 2016;Straatman et al 2018;van der Wel et al 2021). This catalogue includes spectra for 4081 galaxies (3741 unique objecs) within 0.6 < z < 1.3.…”
Section: Star-formation Historymentioning
confidence: 99%
“…In Figure 15 we plot our sample as a combined median where σ is the median of all the line moment measurements presented in Section 3.2, which is 260±21 km s −1 . As a comparison measurements of local ETGs that are based on the MASSIVE (Davis et al 2019) and ATLAS 3D (Cappellari et al 2013) surveys are shown, as well as the quiescent galaxies (D n 4000> 1.55; Kauffmann et al 2003;Wu et al 2018) at z = 0.6 − 1.0 based on the LEGA-C survey (van der Wel et al 2021;Wu et al 2021) and some compiled z ∼ 2 − 4 spectroscopically confirmed quiescent galaxies (Stockmann et al 2020;Valentino et al 2020). The results from the simi-8 re = 1.68h for an exponential disk profile (Chen et al 2015) lar analyses of mostly fainter SMGs presented by Birkin et al (2021) are also shown.…”
Section: Connecting To the Descendantsmentioning
confidence: 99%